1995
DOI: 10.1007/bf00874139
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate reduction by a syntrophic propionate-oxidizing bacterium

Abstract: The syntrophic propionate-oxidizing bacterium MPOB was able to grow in the absence of methanogens by coupling the oxidation of propionate to the reduction of sulfate. Growth on propionate plus sulfate was very slow (mu = 0.024 day-1). An average growth yield was found of 1.5 g (dry weight) per mol of propionate. MPOB grew even slower than other sulfate-reducing syntrophic propionate-oxidizing bacteria. The growth rates and yields of strict sulfate-reducing bacteria (Desulfobulbus sp.) grown on propionate plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…hungateii, strain MPOBT had a growth rate on propionate of approximately 0.17 d-l. In pure culture, lower growth rates were observed; 0.09 d-' during fermentative growth on fumarate and 0.024 d-' during growth on propionate and sulfate (15). Both c-and b-type cytochromes as well as the menaquinones MK-6 and MK-7 were present in fumarate-grown cells.…”
Section: Physiological Characterizationmentioning
confidence: 92%
See 1 more Smart Citation
“…hungateii, strain MPOBT had a growth rate on propionate of approximately 0.17 d-l. In pure culture, lower growth rates were observed; 0.09 d-' during fermentative growth on fumarate and 0.024 d-' during growth on propionate and sulfate (15). Both c-and b-type cytochromes as well as the menaquinones MK-6 and MK-7 were present in fumarate-grown cells.…”
Section: Physiological Characterizationmentioning
confidence: 92%
“…A mesophilic bacterium (strain MPOB') enriched by us on propionate was able to ferment fumarate to succinate and carbon dioxide without a syntrophic partner (12). This strain could oxidize propionate by using fumarate or sulfate as electron acceptors (12,15 pionate by the use of HS-CoA transferase (1 1). 16s rRNA sequence analysis of S. wolinii, S. pfennigii, strain HP1.l and strain MPOBT revealed that these syntrophic bacteria are closely related and belong to the delta subclass of Proteobacteria (3,4,19).…”
Section: Introductionmentioning
confidence: 99%
“…(j) At day 43 of the experiment reported by Kuijk and Stams (1995, their fig. 1); the growth medium has a pH of 7 and contains the following ions: 5.6 mmolal ammonium, 47.6 mmolal bicarbonate, 0.8 mmolal Ca 2ϩ , 13.2 mmolal Cl Ϫ , 3.0 mmolal K ϩ , 0.5 mmolal Mg 2ϩ , 62.7 mmolal Na ϩ , and 6.0 mmolal phosphate.…”
Section: Available Energymentioning
confidence: 98%
“…The ability to use sulphate as a terminal electron acceptor is a characteristic that strain TPO shares with other mesophilic, nonsporulating, syntrophic, propionate-oxidizers (Wallrabenstein et al, 1995 ;Van Kuijk & Stams, 1995). On the basis of the enzyme measurements shown in Table 3, it seems that strain TPO uses the methylmalonylCoA pathway for syntrophic propionate oxidation.…”
Section: Comparison Of Strain Tpo With Other Syntrophic Organismsmentioning
confidence: 99%